Face Masks in Young Children During the COVID-19 Pandemic: Parents' and Pediatricians' Point of View - Assathiany, Rémy; Salinier, Catherine; Béchet, Stéphane; Dolard, Claire; Kochert, Fabienne; Bocquet, Alain; Levy, Corinne (Frontiers in Pediatrics, 2021)
Background: In countries with high SARS-CoV-2 circulation, the efforts to keep schools open represented one of the most important challenge. In France, to keep schools open, wearing a face mask has been mandatory for children from age 6 years since November 2020. Here, we surveyed both parents and pediatricians to evaluate the acceptability and tolerance of this measure for children. Methods: Via their websites, the French Association of Ambulatory Pediatrics administered two online surveys for parents and pediatricians. Results: Among the 2954 questionnaires for the parents’ survey, the reasons for wearing a mask were understood by 54.6% of parents. The parents applied this measure because it was mandatory (93.4%) even if they disagreed (63.3%). When interviewed by parents, children said they ‎were usually embarrassed (80.9%) by the mask. The main symptoms or changes of behavior attributed to the mask according to parents were headache (49.0%), speaking difficulties (45%), change in mood (45.2%) and respiratory disorders (28.1%). When the parents complained about the mask (64.3%), the main drawbacks were related to fog on glasses (reported by 68.2% of pediatricians), respiratory discomfort (reported by 53.1% of pediatricians), cutaneous disorders (reported by 42.4% of pediatricians) and headaches (reported by 38.2% of pediatricians). Conclusion: Despite the many inconveniences reported, children agree to wear the mask better than their parents think. Pediatricians should sufficiently take the opportunity during the consultation to further explain the reasons for wearing the mask because their pedagogical role is crucial.